2008
DOI: 10.1380/ejssnt.2008.246
|View full text |Cite
|
Sign up to set email alerts
|

Spin Reorientation Transition of Fe Ultra-Thin Films on Pd(001) Studied by X-Ray Magnetic Circular Dichroism Spectroscopy

Abstract: We investigated the magnetic anisotropy of bare and Pd-capped Fe ultra-thin films on the Pd(001) single crystal substrate using soft X-ray magnetic circular dichroism (XMCD) spectroscopy. XMCD spectra indicate that the spin reorientation transition (SRT) occurs in Fe/Pd(001). It is suggested that the SRT in Fe/Pd (001) is related to the film morphology. In Pd/Fe/Pd(001), in-plane magnetic anisotropy was observed. No evidence of perpendicular magnetic anisotropy was obtained, which is in contrast to the L10-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The competition between the FePd-IMA and the Co/Pt-PMA causes the thickness-dependent SRT to alter from a polar to a longitudinal direction as the thickness of the FePd capping layer increases, as shown in Figure . Similar thickness-dependent SRT behavior has been reported in magnetic thin film multilayers of various compositions, including Fe/Pd(001) and Co 50 Pd 50 /Al 2 O 3 (0001) . SRT behavior is usually dominated by the competition between the surface/interface-contributed PMA and the IMA; thus, the critical thickness for SRT is determined by the intrinsic surface/interface-contributed PMA and is usually difficult to change.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The competition between the FePd-IMA and the Co/Pt-PMA causes the thickness-dependent SRT to alter from a polar to a longitudinal direction as the thickness of the FePd capping layer increases, as shown in Figure . Similar thickness-dependent SRT behavior has been reported in magnetic thin film multilayers of various compositions, including Fe/Pd(001) and Co 50 Pd 50 /Al 2 O 3 (0001) . SRT behavior is usually dominated by the competition between the surface/interface-contributed PMA and the IMA; thus, the critical thickness for SRT is determined by the intrinsic surface/interface-contributed PMA and is usually difficult to change.…”
Section: Resultssupporting
confidence: 63%
“…In Sander et al’s study, hydrogen-induced reversible SRT was observed in ultrathin Ni films; hydrogen adsorbed on the surface and thus brought about the surface lattice relaxation, leading to the SRT through the change of magneto-elastic anisotropy. , However, this phenomenon was observed in a UHV system and is far from the application in the ambient environment. In the latest decade, the hydrogen-induced reversible change in magnetism has been studied in many systems, which are mostly correlated with the Pd element for catalyzing the dissociation of hydrogen molecules. ,,,,,, Hydrogen absorption into the volume of nanometer-thick CoPd alloy film resulted in considerable change in magnetic coercivity, magnetic anisotropy energy (MAE), magnetic domain revolution, etc. In magnetic systems with small perpendicular MAE or canted MAE, hydrogen-induced SRT from PMA to IMA could possibly be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that a spin reorientation transition (SRT) occurs from the perpendicular to the in-plane direction with increasing Fe thickness for Fe/Pd(001), while no such SRT occurs for 1 ML Pd-capped Fe/Pd(001); however, the microscopic origin of the magnetic anisotropy remained unsolved. 24 In this paper, detailed experimental and theoretical studies of interface atomic structures, magnetic anisotropy, and electronic structures of Fe and Pd/Fe monatomic films on Pd(001) are presented. In order to analyze the interface atomic structures, quantitative low-energy electron diffraction analysis (LEED I -V ) was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Such perpendicular anisotropy (PMA) has been observed in ultra thin, uncapped Pd/Fe bilayers 30 but is normally associated with thicker Fe films grown at low temperature 31,32 . For Pd capped Fe films deposited at 300 K no PMA has been observed and the easy axis remains confined in the plane 13,33,34 . We thus conclude that PMA is an unlikely source of the non-collinear arrangement and an alternative explanation is required.…”
Section: Resultsmentioning
confidence: 98%